Peningkatan Self-Efficacy Pasien Penyakit Ginjal Kronis yang Menjalani Hemodialisis melalui Therapeutic Patient Education - Dewin Safitri; Nurul Jamil (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2024)
Introduction: Self-efficacy is reported as the factor that most influences hemodialysis patient adherence. Interventions to improve self-efficacy have been developed, including through education. The education provided must be structured and include psychosocial aspects to increase self-efficacy, one of the interventions that can be done is Therapeutic Patient Education (TPE). Objectives:  This study aims to determine the effectiveness of therapeutic patient education in Increasing the self-efficacy of patients with chronic kidney disease who are undergoing hemodialysis. Methods: This type of research is a Quasy-Experiment with a pre-test and post-test without a control group approach. 63 respondents were involved in the study. The inclusion criteria in this study were patients who regularly attended hemodialysis sessions, aged 18-65 years, and underwent hemodialysis for more than 3 months, while the exclusion criteria included patients who experienced intradialytic complications and patients who were not willing to become respondents. Data collection used the General Self-Efficacy Scale. Bivariate analysis used paired t-test. Results: Bivariate analysis using the paired t-test found that there was a difference in mean self-efficacy between before (mean 26.70, SD 5.732) and after the Therapeutic Patient Education (TPE) intervention (mean 33.24, SD 4.102, t = 16.393, df 62). The value of p=0.000 (<0.05) indicates that the Therapeutic Patient Education (TPE) intervention is effective in increasing the self-efficacy of chronic kidney disease patients undergoing hemodialysis. Conclusions:  Therapeutic Patient Education (TPE) effectively increases the self-efficacy of chronic kidney disease patients undergoing hemodialysis.